2019
DOI: 10.1002/aur.2159
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of the repetitive behavior scale‐revised using confirmatory factor analysis in children with autism

Abstract: Research examining restricted and repetitive patterns of behavior or interests (RRB) in autism spectrum disorder (ASD) has increased our understanding of its contribution to diagnosis and its role in development. Advances in our knowledge of RRB are hindered by the inconsistencies in how RRB is measured. The present study examined the factor structure of the Repetitive Behavior Scale-Revised (RBS-R) in a sample of 350 children with ASD ages 2-9. Confirmatory factor analysis designed for items with categorical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
3
28
0
1
Order By: Relevance
“…For instance, restricted interests are thought to be a maladaptive coping response to anxiety (17), whilst insistence on sameness behaviours may enable one to control their environment and thus buffer the effect of anxiety (21). These distinctions are consistent with results of factor analyses which have found restricted interests and insistence on sameness behaviours to be distinct subtypes (22)(23)(24). Thus, it is critical to examine these subtypes individually in order to clarify their differential relationship with anxiety.…”
Section: Rrb Subtypes and Anxietymentioning
confidence: 58%
“…For instance, restricted interests are thought to be a maladaptive coping response to anxiety (17), whilst insistence on sameness behaviours may enable one to control their environment and thus buffer the effect of anxiety (21). These distinctions are consistent with results of factor analyses which have found restricted interests and insistence on sameness behaviours to be distinct subtypes (22)(23)(24). Thus, it is critical to examine these subtypes individually in order to clarify their differential relationship with anxiety.…”
Section: Rrb Subtypes and Anxietymentioning
confidence: 58%
“…The results of this study provide support for the validity of the RSM and IS subscales of the RBS-R Caregiver Report in adolescents and adults, extending previous literature primarily conducted in child samples. 12,22,45 Results also provide initial evidence for the use of the RBS-R Self-Report to assess these behavioral domains. However, among participants with both caregiver and self-report forms, RSM scores were only moderately correlated and IS scores were not meaningfully related-suggesting that although the factor validity may be supported, the constructs measured by the scales might differ.…”
Section: Discussionmentioning
confidence: 69%
“…Not only is it important to understand changes in RRBs across time in FXS, it is also critical to assess how effective the RBS-R can detect change in FXS through test-retest reliability. There have been several psychometric analyses of the RBS-R in ASD [40][41][42][43]; however, to the authors knowledge, there has been no work to date assessing the test-retest reliability of the RBS-R. Of note, the RBS-R subscales were all significantly correlated with the RRB scale of the SRS-2, adding to the validity of the measure in a sample with FXS. This is important given the increased need and interest for identifying valid and reliable measures that accurately quantify the core phenotypic symptoms of FXS for clinical trials [28,44].…”
Section: Discussionmentioning
confidence: 94%
“…A recent psychometric analysis across a variety of proposed models for interpreting the RBS-R provided continued evidence to support the use of a five-factor model. Hooker et al [43] reported higher reliability across factors, with little difference between extracted scores and summed scores, and small, significant associations with diagnostic measures using the five-factor approach. Therefore, the present study chose to use the five-factor model identified by Bishop and colleagues [42], which is consistent with previous work examining RRBs in young boys with FXS [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation